INTERDISCIPLINA, COMUNIDAD Y REDES: UNA EXPERIENCIA RADIAL - Isabel Dávila; Marcelo Della Mora (European Scientific Journal, ESJ, 2015)
In this study, we experienced oriented radial transmission and discussed topics related to health and psychology from a broad interdisciplinary perspective, dynamic learning, and questions described. The radio program is focused at the wider community, and only to professionals in the field "psi" i.e. an ongoing dialogue between the listeners which are the real social actors and the privileged invited specialists. Thus, it creates a space by which it promotes words to share the concerns of interest of the whole society.